What successful teachers do : 101 research-based classroom strategies for new and veteran teachers - Glasgow, Neal A.; Hicks, Cathy D. (Thousand Oaks, Calif. : Corwin Press, 2009)
From the Publisher: Providing classroom applications, precautions, and references, this updated edition translates the latest research into 101 strategies for successful instruction for new and veteran teachers.
Includes bibliographical references and index.
Keywords: Effective teaching; Motivation in education; Pédagogie.